2016
DOI: 10.31018/jans.v8i2.873
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Citrus sinensis (masumbi) cultivation in Haryana State, India

Abstract: The empirical study on prospects of Citrus sinensis cultivation by farmers indicated that overall prospects of masumbi (C. sinensis) crop were medium to high since 77.5% respondents belonged to these categories. Majority of respondents agreed that better market facilities (weighted mean score 2.72), increased purchasing power of people (2.65), better fruit quality (2.62), better economic return (2.53) and increase in demand of fruit were the major prospective aspects for its wider adoption (2.53), whereas bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Whereas, CSA helps to escape drought and CSA helps to reduce GHG emissions, ranked fifth, and sixth with WMS 1.62 and 1.6, respectively. This result is in line with Kumar et al (2016) and Rohila et al (2018). Furthermore, participants in the focus group discussion, stated that local communities have practiced and are well aware of CSA practices such as physical soil and water conservation activities such as mulching, cultivating improved varieties, applying animal dungs, and water harvesting through the use of ponds.…”
Section: Farmers' Awareness About Csa Practicessupporting
confidence: 68%
“…Whereas, CSA helps to escape drought and CSA helps to reduce GHG emissions, ranked fifth, and sixth with WMS 1.62 and 1.6, respectively. This result is in line with Kumar et al (2016) and Rohila et al (2018). Furthermore, participants in the focus group discussion, stated that local communities have practiced and are well aware of CSA practices such as physical soil and water conservation activities such as mulching, cultivating improved varieties, applying animal dungs, and water harvesting through the use of ponds.…”
Section: Farmers' Awareness About Csa Practicessupporting
confidence: 68%
“…Low level of prospects may be in deprivation of better technical support linked with strawberry. The present study gets support from Kumar (2016) who reported that majority of farmers has medium (57.5%) prospects level followed by 22.5% low level and only 20.0% to high level. In nutshell, 77.5% of the respondents had prospects of C. sinensis cultivation from medium to high level.…”
Section: Overall Prospects Of Strawberry Cultivation Technologysupporting
confidence: 81%